A review of Cryptosporidium spp. and their detection in water - Hassan, Eman M (Water science and technology : a journal of the International Association on Water Pollution Research, 2021)
Cryptosporidium spp. are one of the most important waterborne pathogens worldwide and a leading cause of mortality from waterborne gastrointestinal diseases. Detection of Cryptosporidium spp. in water can be very challenging due to their low numbers and the complexity of the water matrix. This review describes the biology of Cryptosporidium spp. and current methods used in their detection with a focus on C. parvum and C. hominis. Among the methods discussed and compared are microscopy, immunology-based methods using monoclonal antibodies, molecular methods including PCR (polymerase chain reaction)-based assays, and emerging aptamer-based methods. These methods have different capabilities and limitations, but one common challenge is the need for better sensitivity and specificity, particularly in the presence of contaminants. The application of DNA aptamers in the detection of Cryptosporidium spp. oocysts shows promise in overcoming these challenges, and there will likely be significant developments in aptamer-based sensors in the near future